Splenic volvulus on ectopic spleen in adults: A case report - Lamiaa Chahidi El Ouazzani, MD; Abdelhamid Jadib, MD; Harouna Siradji, MD; Anas El Wassi, MD; Romaissa Boutachali, MD; Houria Tabakh, MD; Abdellatif Siwane, MD; Najwa Touil, MD; Omar Kacimi, MD; Nabil Chikhaoui, MD (Radiology Case Reports, 2022)
Ectopic spleen is a rare clinical entity characterized by splenic hypermobility which may be congenital or acquired. The spleen may be migrated to different positions in the peritoneum. The main complication is pedicular torsion with splenic volvulus, presenting as an emergency abdominal surgery. We present and discuss a case of ectopic and twisted spleen resulting in complete splenic infarction, diagnosed by ultrasound, confirmed by CT scan and treated by splenectomy.